2003
DOI: 10.1002/ajh.10454
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in a patient with β‐thalassemia major: First report

Abstract: Thalassemia is the most common hereditary anemia throughout the world. Survival in its most severe long-term form, b-thalassemia major, has significantly risen in the last decades. Cardiac morbidity-heart failure and dysrhythmias-is still the most common cause of mortality in these patients. We describe herein a case of myocardial infarction with normal coronary arteries in a 48-year-old patient with b-thalassemia and no other recognized risk factors for coronary artery disease. Thromboembolic phenomena, a kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Limited data exist on the atherogenic risk in b-TM. The first documented case of myocardial infarction in a 48-year-old patient with b-TM was reported by Fridlnder and Rund (31). They reported that endothelial dysfunction acts in combination with arterial stiffening to amplify the risk of premature atherosclerosis in b-TM.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data exist on the atherogenic risk in b-TM. The first documented case of myocardial infarction in a 48-year-old patient with b-TM was reported by Fridlnder and Rund (31). They reported that endothelial dysfunction acts in combination with arterial stiffening to amplify the risk of premature atherosclerosis in b-TM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite phenotypic differences between patients with β-TI and β-thalassemia major, which include blood transfusion requirements and features of cardiac complications, vascular disease is relatively common in both thalassemia phenotypes and appears to have a concordant pattern in that both patient groups are protected from coronary artery disease but prone to strokes, thromboembolism, or both [1,2,3,4]. In general, however, the cardiovascular risk profile of patients with β-TI has been inadequately investigated [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, a differential protection of the coronary arterial bed by very low plasma LDL levels in concert with other (e.g. micro-erythrocyte or rheological) factors is possible [2,3,4]. The surprisingly low incidence of coronary events in view of the high incidence of noncoronary events may thus reflect a magnification of existing differences between carotid and coronary artery disease in terms of the histopathophysiology and impact of serum cholesterol levels [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusion-dependent and transfusion-related chronic complications are typically found in the thalassemia major genotype, regardless of whether the thalassemia is α or β. In a previous study, myocardial infarction and coronary artery disease are established complications in transfusion dependent thalassemia patients like α/β thalassemia major or intermedia with more severity clinical manifestations, and thalassemia-related hemolytic anemia or hypercoagulative states are possible explanations [3][4][5].…”
Section: Introductionmentioning
confidence: 94%